2012
DOI: 10.1021/jm300828h
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Less Lipophilic Riminophenazine Derivatives for the Treatment of Drug-Resistant Tuberculosis

Abstract: Clofazimine (CFZ), a member of the riminophenazine class, has been studied in clinical trials for the treatment of multidrug-resistant tuberculosis (MDR-TB). CFZ has several side effects which can be attributed to its extremely high lipophilicity. A series of novel riminophenazine analogues bearing a C-2 pyridyl substituent was designed and synthesized with the goal of maintaining potent activity against Mycobacterium tuberculosis (M. tuberculosis) while improving upon its safety profile by lowering the lipoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…This series of compounds, exemplified by TBI-1004 (Figure 1), displayed potent antituberculosis activity, reduced lipophilicity, and improved pharmacokinetic profiles as compared to CFZ [8]. We also concluded that an electron-withdrawing group at the para-position of the phenyl ring at the N-5 position was beneficial to antituberculosis activity [9]. Previously, O'Sullivan and coworkers found that compounds bearing a 3,4-dichlorophenyl or 3,4,5-trichlorophenyl group at the N-5 position and a tetramethylpiperidyl group at the C-3 position, such as compound B4100 (Figure 1), possessed improved antituberculosis activity as compared to CFZ [10,11].…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…This series of compounds, exemplified by TBI-1004 (Figure 1), displayed potent antituberculosis activity, reduced lipophilicity, and improved pharmacokinetic profiles as compared to CFZ [8]. We also concluded that an electron-withdrawing group at the para-position of the phenyl ring at the N-5 position was beneficial to antituberculosis activity [9]. Previously, O'Sullivan and coworkers found that compounds bearing a 3,4-dichlorophenyl or 3,4,5-trichlorophenyl group at the N-5 position and a tetramethylpiperidyl group at the C-3 position, such as compound B4100 (Figure 1), possessed improved antituberculosis activity as compared to CFZ [10,11].…”
Section: Introductionmentioning
confidence: 81%
“…The most compounds were prepared based on the previously published protocols [9,12]. Nitro compounds 2a-d were synthesized from commercially available 2-fluoronitrobenzene (1) and aryl amines via aromatic nucleophilic substitution.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Mainly, Mtb developed resistance to pyrazinamide with alteration(s) in cell wall synthesis. 7,8 In this scenario, the development of a novel well-tolerated and emulating anti-mycobacterial agent, for the control of MDR, XDR or TDR Mtb, is a dire necessity. Peptidoglycan layer is the major component of Mtb bacterial cell wall providing shape and rigidity, as in eubacteria.…”
Section: Introductionmentioning
confidence: 99%